Effect of the claw disorders on production performance in dairy cattle - Vlček, Michal; Kasarda, Radovan (Acta Agraria Debreceniensis, 2016)
The aim of the study was the influence of claw disorders on production traits in dairy cattle. Observed were claw traits as claw angle, claw length, heel index, claw height, claw diagonal and claw width. Right hind claw after functional trimming was evaluated. Occurrence of claw disorders like interdigital dermatitis and heel erosion (IDHE), digital dermatitis (DD) and sole ulcer (SV) as well as the progress of disease were observed. Basic summary and variation statistics was performed by the SAS software. Two herds were included in the study. Holstein dairy cows (n=101) produced 11 875 kg of milk, 468 kg (3.94%) of fat and 396 kg (3.34%) of proteins. Holstein cows were affected with IDHE in 22 cases, with DD in 6 cases and with sole ulcer in 10 cases. Slovak Simmental dairy cows (n=101) produced 5834 kg of milk, 258 kg (4.44%) of fat and 209 kg (3.59%) of proteins. Slovak Simmental cows were affected with IDHE in 8 cases, with DD in 5 cases and with sole ulcer in 19 cases. Observed was that claw disorders caused deviations of milk production.